Factors influencing the environmental accounting disclosure practices for sustainable development: A systematic literature review - Mondal, Md. Saheb Ali; Akter, Nazma; Polas, Mohammad Rashed Hasan (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study aims to synthesize a testable conceptual framework that illustrates the link between various factors and environmental accounting disclosure practices. Research methodology: A systematic review approach was used to examine publications published from 2001 to 2023. Only the referenced studies were employed as secondary data to identify the factors for synthesizing the conceptual framework. Results: Most publications were studies on emerging nations and showed an expanding trend in disclosures. The findings showed that firm size, profitability, leverage, industry type, and ownership are critical motivators of environmental accounting disclosure (EADs). Moreover, this study summarizes the intriguing concerns not addressed through a conceptual framework. This indicates a possible hypothetical link between these factors for future studies on EADs. Future reviews could boost firms' EADs to help society achieve clean and healthy environments. Originality: The two conceptual frameworks proposed in this study provide new insights into future research and management ramifications.